Determinants of malnutrition in critically ill patients admitting to ICU in Iran - Azadbakht, Leila; Abbasi, Saeid; Hajishafiee, Maryam; Feizi, Awat; Mohajeri, Gholamreza; Nemani, Felorens; Entezari, Mohammad Hassan; Kazemi, Rezvan; Askari, Gholamreza; Samadanian, Fatemeh; Adibi, Peyman (Progress in Nutrition, 2019)
Background and aim: Patients in Intensive Care Unit (ICU) face with major challenges including malnutrition, immune dysfunction, severe infections, multiple organ dysfunction and death. This study was undertaken to evaluate the nutritional status of ICU inpatients receiving nutritional support in Isfahan, Iran. Methods: This cross sectional study was conducted among patients admitted to medical and surgical ICU wards. Nutritional status was assessed via measuring anthropometric indices, laboratory data and medical history by a registered dietitian. Biochemical indicators representing blood values, glycemic status and lipid profile, pulmonary, hepatic and renal function were measured. Malnutrition was assessed according to albumin levels and ideal body weight within 4 categories. Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS, version 16). Results: In this study, decreased level of albumin, total protein and phosphorus were related to malnutrition. Albumin and total protein levels were significantly different within 4 subcategories of patients with more than 90% of ideal body weight (p